Implementasi Kebijakan Pemerintah Melalui Website Sp4n-Lapor Di Sinas Pekerjaan Umum Bina Marga Provinsi Jawa Timur - Evita Maharani; Muhammad Agus Muljanto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
The management of public complaints plays an important role in transparent and accountable governance. The Government of the Republic of Indonesia introduced the National Public Service Complaint Management System–People's Online Aspiration and Complaint Service (SP4N-LAPOR) as an official channel that facilitates public complaints with a higher level of courage and involvement through digital mechanisms. The main purpose of this study is to explore and analyze in detail the implementation of the SP4N-LAPOR website at the East Java Provincial Highway Public Works Office, especially in managing and responding to complaints related to road infrastructure, damaged road conditions, and drainage systems. The research methodology adopts a qualitative descriptive approach, with an analytical foundation that refers to the policy implementation theoretical framework of George C. Edward III, which emphasizes four crucial factors, namely communication, resources, executive disposition, and overall bureaucratic structure. Research data was obtained through secondary data in the form of official agency documents, laws and regulations, reports, and literature relevant to SP4N-LAPOR. The results of the study show that the implementation of the SP4N-LAPOR website at the East Java Provincial Highway Public Works Office has generally been running in accordance with applicable provisions and supported by a clear legal basis and SOPs. In terms of communication, implementation is still not optimal due to limited socialization to the community. From the aspect of resources, special apparatus has been available as an admin of SP4N-LAPOR, limited budget constraints and high workload still make it difficult to respond to complaints. In terms of disposition, management apparatus shows a responsive and responsible attitude, although there are still differences in the level of commitment between employees. From the aspect of bureaucratic structure, the division of authority and SOPs has helped the complaint management process run more systematically, although coordination between units still needs to be improved. Therefore, it is necessary to increase socialization, strengthen resources, and improve bureaucratic coordination so that the implementation of SP4N-LAPOR can run more optimally.